Kewajiban Hukum Vaksinasi Dalam Perpres No.14 Tahun 2021 Perspektif HAM di Indonesia - Wahyukurnianingsish; Beti Amalia; Ahmadi Hasanuddin Dardiri (Jurnal Hukum dan Etika Kesehatan, 2022)
Indonesia is currently facing a COVID-19 emergency situation. The Indonesian government has implemented a vaccination program to suppress the spread of COVID-19 as regulated in Presidential Decree No. 14 of 2021 concerning the procurement of vaccines and the implementation of COVID-19 vaccination which includes the obligation to vaccinate. This vaccination obligation reaps the pros and cons in society. People who refuse to think that the obligation to vaccinate against human rights. According to them, the choice to vaccinate is the right of every individual to exercise or not to exercise their rights. On that basis, we conducted a study of mandatory vaccination from a human rights perspective. The purpose of this study is to find out how the Legal Review of Vaccination Obligations in the Perspective of Human Rights in Indonesia. The analytical method used is a descriptive analytic study using a normative juridical approach. The collected data was then analyzed by deductive method. The results of the study indicate that the obligation to vaccinate the community does not violate human rights as stated in Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia which regulates the limitation of human rights. Basically, the nature of human rights is grouped into two, namely Derogable Right and Non Derogable Right. The obligation to vaccinate is actually a way to protect the human rights of others, namely the right to life. The right to life is part of human rights which are non-derogable rights. The presence of the state in guaranteeing the right to life is implemented in the implementation of vaccination obligations. The absence of the obligation to vaccinate is actually a violation of human rights because it overrides the community's right to life. kewajiban vaksinasi, hak asasi manusia, hak hidup